Edukasi Risiko Knee Osteoarthritis dalam Upaya Meningkatkan Kualitas Hidup pada Komunitas Lansia - Reni Dwiyanti; Agashi Al’ Ainaa Almardyah; Cindy Dwi Fitria; Diva Amanda Oliviyan; Nabila Randy Dhiyanisa; Najah Fadiya Humaira; Bayu Prastowo; Diyah Mulia Handayani; Sucik Istiyaningsih (Health Care : Journal of Community Service, 2024)
An elderly person is someone who is 60 years old and above. As we age, many degenerative diseases such as movement disorders in the knee joint or knee osteoarthritis (KOA). This condition causes a decrease in body function and can reduce quality of life, such as limited space for movement, decreased work ability, and severe pain. This Community Service activity was carried out at the Tamanharjo Elderly Community, Malang with 30 elderly participants. This activity uses the Service Learning (SL) method with the achievement of service indicators through pre and post-test. These indicators include definitions, signs and symptoms, risk factors and KOA rehabilitation.  The pre-test results showed 5% to 10%.  While the post-test shows results up to 95%. So that this service is able to increase elderly knowledge related to KOA as an effort to improve quality of life.